Modal Sosial Pembangunan SDM Masyarakat Bali - I Gusti Ayu Wimba (Bali Membangun Bali: Jurnal Bappeda Litbang, 2019)
During this time, the government and the community in implementing development, explicitly only prioritize economic capital and human capital in an individual perspective only. Not many people have highlighted the role of social capital, which is a necessity, in maintaining the results of development that have been carried out. Mainly, Balinese social capital which is hierarchically shaped through values that are invested from an early age, will grow into an accumulation of social capital which will later contribute positively in maintaining a conducive atmosphere in developing human resources for the Balinese people.